A ROS/Gazebo based method in developing virtual training scene for upper limb rehabilitation - Zhijiang Du; Yixuan Sun; Yanyu Su; Wei Dong (2014 IEEE International Conference on Progress in Informatics and Computing, 2014)
Virtual Reality (VR) presents a promising future in the field of rehabilitation due to its advantages brought to the training process as is indicated in many articles and researches. In this paper, we describe a novel method in developing a virtual training environment for a 5 degrees of freedom (DOF) upper limb rehabilitation robot which has been designed to help provide assistance for patients who survive stroke but remain hemiplegic to complete rehabilitation exercise. The method involved utilizes ROS (Robot Operating System) and Gazebo (a multi-robot simulator) to set up an interesting virtual scene of daily life in a 3D world to facilitate the patients to move their affected arms with synchronous visual feedback and interact with the virtual training task. The control method of human model in the virtual world and the communication mechanism between the host machine which controls movement of the real robot and the master machine which runs the VR will be introduced. Finally, a virtual training environment containing reaching task set in a modern kitchen is presented.